Exploring the world of micro sculptures - subfossil Cladocera remains under the SEM - Izabela Zawiska; Edyta Zawisza; Marta Wojewódka; Artem Y. Sinev (Advances in Oceanography and Limnology, 2016)
The scanning electron microscope (SEM) is widely used for the identification of microstructural characteristics and morphology of different microorganisms. Common procedures are based and developed for remains of living species. This paper presents an effective method for drying and preparing subfossil Cladocera remains for SEM observation, which has been recently adapted and tested on several samples originating from different American and European lakes. This method results to be fast and cheap, as it excludes the use of expensive and toxic reagents. Moreover, it allows to recognize the micro sculpture and other species specific characteristics present on the different body parts of the Cladocera remains. The present contribution provides 29 high quality pictures of 12 cladoceran species at magnification between 200x and 11,000x. SEM images reveal  that the patterns observed on the shells under the light microscope actually are always three dimensional structures.